Green Plant Pigment, Chlorophyllin, Ameliorates Non-alcoholic Fatty Liver Diseases (NAFLDs) Through Modulating Gut Microbiome in Mice - Yang, You; Jiang, Xile; Pandol, Stephen J.; Han, Yuan-Ping; Zheng, Xiaofeng (Frontiers in Physiology, 2021)
Non-alcoholic fatty liver diseases (NAFLDs) along with metabolic syndrome and Type-2 diabetes (T2D) are increasingly prevalent worldwide. Without an effective resolution, simple hepatic steatosis may lead to non-alcoholic steatohepatitis (NASH), characterized by hepatocyte damage, chronic inflammation, necrosis, fatty degeneration, and cirrhosis. The gut microbiome is vital for metabolic homeostasis. Conversely, dysbiosis contributes to metabolic diseases including NAFLD. Specifically, diet composition is critical for the enterotype of gut microbiota. We reasoned that green pigment rich in vegetables may modulate the gut microbiome for metabolic homeostasis. In this study, C57BL/6 mice under a high fat diet (HFD) were treated with sodium copper chlorophyllin (CHL), a water-soluble derivative of chlorophyll, in drinking water. After 28 weeks of HFD feeding, liver steatosis was established accompanied by gut microbiota dysbiosis, intestinal impairment, endotoxemia, systemic inflammation, and insulin resistance. Administration of CHL effectively alleviated systemic and intestinal inflammation and maintained tight junction in the intestinal barrier. CHL rebalanced gut microbiota in the mice under high fat feeding and attenuated hepatic steatosis, insulin resistance, dyslipidemia, and reduced body weight. Fecal flora transplants from the CHL-treated mice ameliorated steatosis as well. Thus, dietary green pigment or the administration of CHL may maintain gut eubiosis and intestinal integrity to attenuate systemic inflammation and relieve NASH.